CODE MIXING ANALYSIS IN THE ANGRY COMMUNITY ON TWITTER - Nuha Fathinah Al Fani (Esteem Journal of English Education Study Programme, 2025)
This research seeks to explore the phenomenon, types, and underlying reasons for the use of two languages (code mixing) within the "angry" community on Twitter. Employing a qualitative descriptive approach with a digital ethnography method, the study collects data through observation, interviews, and field notes. The primary data sources include five tweet threads that demonstrate the use of two languages, as well as interview responses from five community members to investigate their motivations for using code mixing on the platform. The analysis identified two types of intra-sentential code mixing: insertion (at the word level) and alternation (at the phrase level). Most instances involved the incorporation of English words or phrases within Indonesian sentences. Based on the interviews, three key reasons emerged for this code mixing: habitual use of both languages in daily life that extends into online communication, a tendency to imitate peers who mix languages, and the desire to practice and enhance their second language proficiency.